Making use of the internet in studying electronic Qur’an in light of the topics of the sciences of the Qur’an and the rules of interpretation is a descriptive and critical study - Yousef A. Baker, El-Ebiary; Mohamed Ataala, Elazab Ali Ismail; Moslim Saeed, M. Al-Othaimin (2020)
The electronic Qur’an that are widespread these days believes that they have not been accurately edited like the papered Qur’an, and scientific committees who specialize in drawing and reading the Qur’an have not supervised their preparation. Therefore, they have not been spared from the errors that are not worthy of the Holy Qur’an of miscarriage, correction, distortion and others. For this and others, it was necessary for us to prepare a comprehensive study of all electronic Qur’ans spread on the Internet, dealing with their most important features, and standing on those scientific and technical shortcomings and lapses in them; to come out with clear results and recommendations for the developers of these Qur’ans in preparation for their implementation, hence this research entitled: “How to benefit from the Internet in studying electronic Qur’ans in light of the topics of the Qur’an sciences and rules of interpretation, a critical descriptive study.” The research has studied and examined (35) electronic Qur’ans for a scientific and technical examination. Through a scientific and technical team; To find out the scientific and technical notes in these Qur’ans. This research falls into an introduction, an introduction, three chapters and a conclusion.